2004
DOI: 10.1002/ppul.20058
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity 20 years after RSV infection in infancy

Abstract: Epidemiological data suggest that respiratory syncytial virus (RSV) infection in early life is a risk factor for later asthma. There are no prospective studies on RSV infection starting from infancy progressing through childhood into adulthood. We followed up a cohort of children, hospitalized for RSV bronchiolitis or RSV pneumonia before age 24 months, until age 18-20 years. The aim of the study was to evaluate early RSV infection as a risk factor for asthma, bronchial reactivity, and lung function abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
5
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 29 publications
9
122
5
8
Order By: Relevance
“…Although the underlying mechanisms whereby reduced Crs leads to RSV hospitalisation are unknown, it is possible that reduced Crs reflects differences in lung characteristics leading to both a severe RSV infection and childhood asthma. Several prospective studies have described the association between RSV bronchiolitis and the development of post-bronchiolitis wheeze [28][29][30]. Our data suggest that besides the severity of the RSV infection, premorbid increased Rrs and decreased Crs also are independent determinants of post-RSV wheeze.…”
Section: Discussionsupporting
confidence: 54%
“…Although the underlying mechanisms whereby reduced Crs leads to RSV hospitalisation are unknown, it is possible that reduced Crs reflects differences in lung characteristics leading to both a severe RSV infection and childhood asthma. Several prospective studies have described the association between RSV bronchiolitis and the development of post-bronchiolitis wheeze [28][29][30]. Our data suggest that besides the severity of the RSV infection, premorbid increased Rrs and decreased Crs also are independent determinants of post-RSV wheeze.…”
Section: Discussionsupporting
confidence: 54%
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Early-life exposure to such pathogens is likely to have lifelong respiratory consequences. Indeed, even in healthy term-born infants, hospitalisation with acute respiratory viruses in early life is associated with increased rates of childhood asthma, wheezing disorders and suboptimal lung function [2931]. While preterm infants are often labelled as asthmatic, the underlying mechanisms of prematurity associated wheeze are likely to be different [32] although the long-term implications of exposure to acute respiratory viruses during early life remains to be elucidated in the preterm population.…”
Section: Preterm Birth and Bronchopulmonary Dysplasia: An Immature Symentioning
confidence: 99%
“…Early-life exposure to severe RSV infection has also been identified as a main contributor in the development of suboptimal lung health and function later in life, with several studies reporting increased risks of late-onset or persistent wheezing phenotypes, asthma diagnosis, and impaired lung function in adolescents and young adults [2931]. Even though the majority of the data on the long-lasting impact of RSV have been based on studies of healthy term-born infants, limited studies have demonstrated increased risk of asthma [68], recurrent wheeze [34,69,70] and lung function impairments [66] in preterm children with a history of RSV-related hospitalisation during infancy.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%